Relationship Between Environmental Degradation, Economic Factors, And Tourism Indicators In Priority Tourism Destination Provinces In Indonesia - Royyan Akbar; Zulfa Emalia (Economics and Digital Business Review, 2025)
The tourism sector is one of the important sectors in increasing economic growth in Indonesia. However, in addition, the tourism sector can also indirectly cause negative effects, namely environmental degradation in the form of carbon emissions caused by several tourism activities. This study aims to analyze the influence of carbon emissions, GRDP which is one of the economic factors, the number of foreign tourists which is one of the tourism indicators, and the population in five provinces that are priority tourist destinations in Indonesia in 2010 - 2019, and also see the long-term influence between related variables. This study uses panel data with a quantitative approach that is analyzed with several tests, including the residual normality test, panel unit root test, cointegration test, and FMOLS test. The results of the study indicate that the GRDP and number of foreign tourists variables have a positive and significant effect, while the energy consumption and population variables have a negative and significant effect. The cointegration and FMOLS tests show that in this study there is a long-term effect between GRDP, the number of foreign tourists, energy consumption, population, and carbon emissions in five priority tourist destination provinces in Indonesia.